2020
DOI: 10.1080/02656736.2020.1756467
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility and safety study of computed tomography-guided percutaneous microwave ablation: a novel therapy for multiple synchronous ground-glass opacities of the lung

Abstract: Ye (2020) A feasibility and safety study of computed tomography-guided percutaneous microwave ablation: a novel therapy for multiple synchronous ground-glass opacities of the lung, International

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 41 publications
(50 reference statements)
2
27
1
Order By: Relevance
“…Given the unprecedented large lesions to be ablated and the combined utility of MWA with ITC in this study, ≥2 ablation antennae and ≥1 Chiba needles were used to cause multiple punctures through the pleura, which could slightly increase the incidence (52.3% vs. 31.9%) and severity (chest tube: 22.7% vs. 11.5%) of pneumothorax ( 7 ). Likewise, the incidence (77.3% vs. 68.2%) and severity (chest tube: 11.4% vs. 3.0%) of pleural effusion in this study were modestly higher than in our previous report, which was associated with severe thermal injury to the pleura due to a higher proportion (38.6%) of lesions involving the pleura or chest wall and a longer ablation time (mean 26.8 min) ( 6 ). The incidence (6.8%) of pulmonary infections, including bacterial (4.5%) and fungal (2.3%) infections corresponded with previously reported rates of 1%–6% ( 16 ).…”
Section: Discussioncontrasting
confidence: 70%
“…Given the unprecedented large lesions to be ablated and the combined utility of MWA with ITC in this study, ≥2 ablation antennae and ≥1 Chiba needles were used to cause multiple punctures through the pleura, which could slightly increase the incidence (52.3% vs. 31.9%) and severity (chest tube: 22.7% vs. 11.5%) of pneumothorax ( 7 ). Likewise, the incidence (77.3% vs. 68.2%) and severity (chest tube: 11.4% vs. 3.0%) of pleural effusion in this study were modestly higher than in our previous report, which was associated with severe thermal injury to the pleura due to a higher proportion (38.6%) of lesions involving the pleura or chest wall and a longer ablation time (mean 26.8 min) ( 6 ). The incidence (6.8%) of pulmonary infections, including bacterial (4.5%) and fungal (2.3%) infections corresponded with previously reported rates of 1%–6% ( 16 ).…”
Section: Discussioncontrasting
confidence: 70%
“…Early evidence gleaned during the past few years suggests that pMWA may be a safe and feasible management strategy for patients with multiple GGOs. 30 Because the etiology of GGOs are so varied, combining with resection may provide a particular advantage in subsequent decision making regarding further completion surgery (eg, anatomical lung resection), medical therapy, or interval surveillance imaging. Similarly, thermal ablation is emerging as an alternative to stereotactic radiation therapy in the treatment of stage 1 non–small cell lung cancer suggesting that the application of iCART may expand to nonmetastatic pulmonary nodules in future.…”
Section: Discussionmentioning
confidence: 99%
“…Image-guided percutaneous thermal ablation, including radiofrequency ablation, microwave ablation (MWA), and cryoablation, has been increasingly used for medically inoperable patients with early-stage lung cancer [ 62 , 63 ]. Recently, these techniques have also been applied in the management of MPLC with promising results [ 64 , 65 ]. Huang et al reported a 100% technical success rate of treating multiple synchronous GGOs with computed-tomography–guided percutaneous MWA, with an acceptable complication rate [ 65 ].…”
Section: Management Of Mplcmentioning
confidence: 99%
“…Recently, these techniques have also been applied in the management of MPLC with promising results [ 64 , 65 ]. Huang et al reported a 100% technical success rate of treating multiple synchronous GGOs with computed-tomography–guided percutaneous MWA, with an acceptable complication rate [ 65 ]. Qu et al further combined electromagnetic navigation bronchoscopy (ENB)-guided MWA with uniportal VATS in 11 patients with multiple GGO, and reported a 100% success rate, with no recurrence observed at follow-up [ 66 ].…”
Section: Management Of Mplcmentioning
confidence: 99%